A prospective feasibility study evaluating the implementation of model-informed precision dosing in critically ill children - Bayraktar, Izgi; Kaşıkcı, Merve; Benek, Zuhal; Allegaert, Karel; Egehan Oruncu, Berna; Kesici, Selman; Bayrakci, Benan; Yalcin, Nadir (Frontiers in Pharmacology, 2026)
Achieving optimal antibiotic exposure in critically ill pediatric patients is difficult due to (their) dynamic physiology and variability. Conventional weight-based regimens often fail to reach pharmacokinetic/pharmacodynamic (PK/PD) targets for narrow therapeutic index agents such as vancomycin and amikacin. Model-Informed Precision Dosing (MIPD), which integrates Bayesian forecasting with population pharmacokinetics (popPK), offers a potentially valuable yet underexplored approach in pediatric intensive care to better attain and sustain target exposure. This study was designed as a prospective, pragmatic feasibility study with a comparator arm, employing observational analyses to evaluate the implementation and methodological performance of MIPD in a tertiary pediatric intensive care unit. Pediatric patients receiving vancomycin or amikacin were managed either with MIPD-guided dosing using a clinical decision support platform or with standard-of-care (SoC) dosing. Primary outcomes included prediction accuracy (a priori vs. a posteriori) and model fit, defined by the agreement between observed and model-predicted concentrations and categorized as poor, intermediate, or good. Secondary outcomes assessed dose optimization, inflammatory response, renal safety, treatment duration, and mortality. Forty-one patients (median age 38.6 months) were enrolled; Patients were initially allocated to either MIPD or SoC; however, the final analytic groups were defined as-treated, with 12 receiving active MIPD-guided dose adjustments and 29 managed under SoC dosing. Some baseline differences were observed between groups, particularly in inflammatory markers. Clinical outcomes were similar between groups, with numerically greater but nonsignificant reductions in CRP and procalcitonin in the MIPD group. However, these findings were confounded by baseline imbalances and should be interpreted cautiously. Model fit remained unchanged in the SoC group but showed modest improvement for vancomycin under MIPD. Larger, multicenter trials are warranted to confirm clinical benefit and optimize implementation in pediatric intensive care.Clinical Trial RegistrationClinicalTrials.gov, identifier NCT07315438.